Inhibition of aquaporin-3 in macrophages by a monoclonal antibody as potential therapy for liver injury - Hara-Chikuma, Mariko; Tanaka, Manami; Verkman, Alan S.; Yasui, Masato (Nature communications, 2020)
Aquaporin 3 (AQP3) is a transporter of water, glycerol and hydrogen peroxide (H 2 O 2 ) that is expressed in various epithelial cells and in macrophages. Here, we developed an anti-AQP3 monoclonal antibody (mAb) that inhibited AQP3-facilitated H 2 O 2 and glycerol transport, and prevented liver injury in experimental animal models. Using AQP3 knockout mice in a model of liver injury and fibrosis produced by CCl 4 , we obtained evidence for involvement of AQP3 expression in nuclear factor-κB (NF-κB) cell signaling, hepatic oxidative stress and inflammation in macrophages during liver injury. The activated macrophages caused stellate cell activation, leading to liver injury, by a mechanism involving AQP3-mediated H 2 O 2 transport. Administration of an anti-AQP3 mAb, which targeted an extracellular epitope on AQP3, prevented liver injury by inhibition of AQP3-mediated H 2 O 2 transport and macrophage activation. These findings implicate the involvement of macrophage AQP3 in liver injury, and provide evidence for mAb inhibition of AQP3-mediated H 2 O 2 transport as therapy for macrophage-dependent liver injury. Aquaporin 3 (AQP3) is a transporter of water, glycerol and hydrogen peroxide, and hydrogen peroxide mediated oxidative stress has been implicated in liver injury. Here, the authors report the development of an anti-AQP3 monoclonal antibody, which alleviates liver injury in multiple mouse models.